Ética, economia e justiça: a escolha social no pensamento de Sen e Smith - Luiz Bernardo Leite Araujo; Fábio dos Santos Creder (DoisPontos, 2013)
This article aims to examine Adam Smith’s deep and broad influence on the thought of Amartya Sen, especially concerning the issue of social justice that pervades the writings of both authors. First, we will analyze Sen’s revision of the work of Smith to refute the interpretation still prevalent, that makes use of certain excerpts from The Wealth of Nations as the main reference in defending the deregulation of markets and in exempting the economic thought from any consideration of moral values, demonstrating how Sen draws on Smith’s ideas to explain the impoverishment of economics when it departs from ethics. Then, we will consider the overwhelming influence of the Smithian thought on Sen’s criticism of the theory of rational choice through his distinctive formulation of the theory of social choice, whose importance was rightly recognized, earning him the Nobel Prize in Economics in 1998.